2022
DOI: 10.1088/2051-672x/ac7737
|View full text |Cite
|
Sign up to set email alerts
|

A roughness calculation method based on milling topography simulation

Abstract: The surface texture and roughness parameters of the workpiece after milling have a greater impact on the performance of the workpiece, so the analysis of the milling topography is particularly important. Firstly, the edge line of the ball end milling cutter was modeled. According to the movement law of the milling process, a complete set of milling topography simulation model was established, and a new influencing factor phase difference is proposed. In addition to the conventional cutting parameters, the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…When the inclination angle was between 0 and 60°, the roughness decreased first and then increased as the angle increased. Zhang et al [ 49 ] established a simulation model for ball-end tool milling to study the relationship between the inclination angle and roughness. The experimental results indicated that when the inclination angle increased from 0 to 30°, the roughness decreased first and then increased.…”
Section: Introductionmentioning
confidence: 99%
“…When the inclination angle was between 0 and 60°, the roughness decreased first and then increased as the angle increased. Zhang et al [ 49 ] established a simulation model for ball-end tool milling to study the relationship between the inclination angle and roughness. The experimental results indicated that when the inclination angle increased from 0 to 30°, the roughness decreased first and then increased.…”
Section: Introductionmentioning
confidence: 99%